Rincones de aprendizaje para niños de 3 a 4 años de nivel inicial - Chicaiza Chicaiza, Vilma Marianela (2016)
This project "Learning Corners for children 3 - 4 years of initial level" aims through the play-work that infants develop different social skills, motor, intellectual and linguistic. The lact of learning corners for initial level limits the efficiency in the teaching and learning of children. The research was conducted at the "NASA" Education Unit at Chisinche neighborhood, Mejia Canton. It was based on a diagnosis of the current situation of the institution, using descriptive methodology from interviews with experts in the Preschool Education Career. Also information was collected by children checklist and fieldnotes, everything based on the qualitative research perspective. The go results reveal that the institution does not have learning corners, so it does not have enough teaching materials for the teaching-learning process. The implementation of learning corners for 3 - 4 years children of initial level, contribute to the improvement of teaching- learning processes for children starting level. The direct beneficiaries of this project will be children 3 - 4 years with a total of 20 children, as well as a teacher and indirect beneficiaries will be the society and parents.